People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Oversight and Supervision of Financial Market Infrastructures-Technical Note. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Note on Oversight and Supervision of Financial Market Infrastructures has been prepared in the context of the Financial Sector Assessment Program for the People's Republic of China-Hong Kong Special Administrative Region (HKSAR). Nine financial market infrastructures (FMIs) operate in HKSAR; the effectiveness of their supervision and oversight is critical in maintaining financial stability. In order to support their objective of consolidating Hong Kong's position as an international financial center, the Hong Kong authorities have fostered the development of sophisticated and multicurrency FMIs. The risks associated with domestic and overseas linkages appear to be adequately managed. Extensive domestic and overseas system linkages have been implemented making HKSAR a regional settlement hub. The legal framework should be amended to explicitly prohibit a domestic clearing house from operating in HKSAR without being recognized as such. The respective legal framework and policy mandate determines the actions of the Hong Kong Monetary Authority and the Securities and Futures Commission as the two regulatory, oversight and supervision authorities for FMIs in HKSAR.